Niveles de compost de residuos de nabo en las características agronómicas y rendimiento de Brassica olerácea L., variedad corazón de buey, Loreto - Flores Sandoval, Laury Elking (2024)
The objective of this research was to evaluate the effect of different doses of compost made from turnip residues on the agronomic characteristics and yield of **Brassica oleracea L.** Cabbage Var. Corazón de Buey, under cultivation conditions in Loreto, Peru. A randomized complete block design (RCBD) with five treatments was used: 30 t/ha (T1), 40 t/ha (T2), 50 t/ha (T3), and 60 t/ha (T4). An analysis of variance (ANOVA) and Tukey's test were conducted to determine significant differences between treatments (p<0.01). The results indicated that higher doses of compost (50 t/ha and 60 t/ha) significantly increased the evaluated variables. In terms of plant height, averages of 27 cm and 29 cm were obtained, respectively, while head weight reached a maximum of 560 g with 60 t/ha. Moreover, the total plant weight was highest in T4 (1100 g), showing significant differences compared to the other treatments. The coefficient of variation for the key variables was below 10%, indicating low experimental variability and high precision in the results. It is concluded that the use of compost made from turnip residues at a dose of 60 t/ha significantly improves the agronomic characteristics and yield of cabbage, representing a sustainable alternative to enhance productivity in agricultural systems.